Antibacterial Efficiency and Phytochemical Assessment of Stereospermum Chelonoides (L.F.) DC Flower and Leaf Mixed Powder Extracts: Life Science-Microbiology - Sangeetha, M.; Anandaraj , B.; Rajan, S. (International Journal of Life Science and Pharma Research, 2022)
Aim of the present study is to evaluate antibacterial efficiency of mixed powder preparation from the leaf and flower of Stereospermum chelonoides and its phytochemical evaluation. Bacterial species tested were isolated from UTI cases and showed multidrug resistance property. Stereospermum chelonoides is one of the medicinal trees worshiped as Holy plants in Thyagaraja Swamy Temple in Thiruvarur. It belongs to the family Bignoniaceae commonly called Sivappu Pathiri. All parts of the plant show a biological efficiency evidenced through various ethnobotanical databases. Traditional healers use this plant as a heal for vomiting, eructation, piles, acidity, diarrhoea, gonorrhoea, loss of taste, malaria and other fevers. Antimicrobial activity was assessed by making use of two bacterial isolates by disc diffusion and drug dilution method. Zone of inhibition, MIC, MBC, Percentage inhibition and IC50 were calculated using standard textual methods. Qualitative and quantitative phytochemicals were assessed by making use of textual procedures. Active principle of the SCMPEE was evaluated by the column chromatography, TLC, LC-MS and NMR methods. Aqueous (SCMPAE) and ethanolic (SCMPEE) extracts produced good antibacterial activity against all the test organisms with efficient MIC and MBC. Percentage of inhibition ranges from 53.1% to 84.2%. Stereospermum chelonoides extracts inhibited the growth of gram negative urinary bacterial isolates with 274.4 μg/ml IC50 for Klebsiella pneumoniae by SCMPEE. Qualitative phytochemical analysis showed the presence of tannins, saponins, terpenoids, triterpenoids, flavonoids, anthraquinones and polyphenols in both the extracts. Active principle assessment indicated the presence of quercetin 3 -O-Glucoside, which could exert antibacterial efficiency via protein precipitation mechanisms. , , , , , ,